If sum of n terms of an arithmetic progression is p n + q n 2 , where p and q are constants, find the common difference.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is a simple approach to this problem.
Now
S
n
=
p
n
+
q
n
2
.
If we replace
n
with
n
−
1
it gives
S
n
−
1
.
So,
S
n
−
1
=
p
(
n
−
1
)
+
q
(
n
−
1
)
2
S
n
−
1
=
p
n
−
p
+
q
(
n
2
−
2
n
+
1
)
S
n
−
1
=
p
n
−
p
+
q
n
2
−
2
q
n
+
q
Now if we subtract
S
n
−
1
from
S
n
we get the nth term
a
n
.
a
n
=
S
n
−
S
n
−
1
a
n
=
p
n
+
q
n
2
−
(
p
n
−
p
+
q
n
2
−
2
q
n
+
q
)
a
n
=
p
n
+
q
n
2
−
p
n
+
p
−
q
n
2
+
2
q
n
−
q
a
n
=
p
+
q
(
2
n
−
1
)
Here we see that any term of an is defined. So, if we replace
n
with
n
−
1
we get
a
n
−
1
.
a
n
−
1
=
p
+
q
(
2
(
n
−
1
)
−
1
)
a
n
−
1
=
p
+
q
(
2
n
−
3
)
Since
a
n
−
1
and
a
n
are consecutive terms of an AP their difference is the common difference of the AP.
a
n
−
a
n
−
1
=
d
d
=
p
+
q
(
2
n
−
1
)
−
(
p
+
q
(
2
n
−
3
)
)
d
=
p
−
p
+
q
(
2
n
−
1
−
2
n
+
3
)
d
=
2
q
Wow, so complicated. Anyway, typo: d = 2 q
Problem Loading...
Note Loading...
Set Loading...
S n = p n + q n 2 T 1 = S 1 = p ( 1 ) + q ( 1 ) 2 = p + q T 2 = S 2 − S 1 = p ( 2 ) + q ( 2 2 ) − ( p + q ) = 2 p + 4 q − p − q = p + 3 q d = T 2 − T 1 = p + 3 q − ( p + q ) = 2 q